A02 Altered epigenetic and transcriptional regulation during striatum-dependent memory in HD mice. (12th September 2022) - Alcalá-Vida, R; Lotz, C; Seguin, J; Decraene, C; Brulé, B; Awada, A; Bombardier, A; Cosquer, B; Pereira de Vasconcelos, A; Brouillet, E; Cassel, J-C; Boutillier, A-L; et al.
Abstract : Epigenetic mechanisms are altered in the striatum of HD patients and mouse models, but how they might contribute to pathogenesis, including cognitive deficits, is unclear. Epigenetic regulation is critical to learning and memory processes, through transcriptional control of gene program promoting neural plasticity. We asked whether memory-associated epigenetic and transcriptional responses were impaired in HD R6/1 mice. To this end, we trained R6/1 mice (and control mice) in an aquatic navigation task, the double H maze, which allows assessing striatum-dependent memory (e.g. egocentric spatial memory). We then generated ChIP-seq, 4C-seq and RNA-seq datasets on striatal tissue of HD and control mice during egocentric memory processing, including memory acquisition and consolidation/recall. Egocentric memory was altered since early symptomatic stage in R6/1 mice, which correlated with dramatic reduction of striatal epigenetic and transcriptional changes induced by memory process. More specifically, multi-omic analysis showed that, during memory acquisition, 3D chromatin re-organization and transcriptional induction at BDNF-related genes were diminished in R6/1 striatum. Moreover, we found that changes in H3K9 acetylation (H3K9ac), which accompanied memory process in normal striatum, were attenuated in R6/1 striatum. Functional enrichment analyses further indicated that altered H3K9ac regulation during late phase of egocentric memory process (e.g. consolidation/recall) contributed to impaired TGFβ-dependent cellular plasticity. Together, this study provides support to the hypothesis that epigenetic dysregulation in HD contributes to cognitive deficits, and shed light on new targets of striatal plasticity, particularly H3K9ac and TFGβ signaling.